OBESITY AS A RISK FACTOR FOR CHRONIC NON-COMMUNICABLE DISEASES - O. M. Drapkina; S. O. Eliashevich; R. N. Shepel (Российский кардиологический журнал)
Among the risk factors of years of life loss, with correction for disability, the leading are arterial hypertension, smoking, high body mass index. Results of large prospective studies confirm the relation of excessive body mass with the increase of cardiovascular risk. Relative risk of cardiovascular disorders (CVD) in obese is comparable to the total impact of BP raise by 20 mmHg. However, most of current CV risk stratification models do not include obesity as one of the risk factors. There are several phenotypes of obesity. Presence of any leads to increased cardiovascular and diabetes (type 2, DM) risk. Metabolically healthy obesity comparing to the situation of comorbid obesity with metabolic syndrome is associated with lower DM risk, but cardiovascular risk is high equally in both obesity phenotypes. Hence, metabolically healthy obesity is not “benign” condition and demands the actions from us, interventions for loss of weight and strict control of modifiable risk factors.